2021
DOI: 10.1002/agg2.20164
|View full text |Cite
|
Sign up to set email alerts
|

An evaluation of biological soil health indicators in four long‐term continuous agroecosystems in Canada

Abstract: The soil microbial community (SMC) and soil organic matter (SOM) are inherently related and are sensitive to land‐use changes. Microorganisms regulate essential soil functions that are key to SOM dynamics, whereas SOM dynamics define the SMC. To expand our understanding of soil health, we evaluated biological and SOM indicators in long‐term (18‐yr) continuous silage corn (Zea mays L.), continuous soybean [Glycine max (L.) Merr.], and perennial grass ecosystems in Ontario, Canada. The SMC was evaluated via este… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 63 publications
1
11
0
Order By: Relevance
“…Although POXc exhibited strong responses to changes in management practices in our short-term analysis, Pérez-Guzmán et al (2021) reported highly variable POXc responses between management treatments in Ontario, Canada, and highlighted the use of more sensitive indicators, such as the combined enzyme assay technique. In addition, our study could not differentiate between pasture, grassland, and forage fields due to the inadequate spatial resolution of the satellite imagery and lack of reliable agricultural land use information.…”
Section: Changes In Toc and Poxc (2015/16 -2019/20)mentioning
confidence: 81%
“…Although POXc exhibited strong responses to changes in management practices in our short-term analysis, Pérez-Guzmán et al (2021) reported highly variable POXc responses between management treatments in Ontario, Canada, and highlighted the use of more sensitive indicators, such as the combined enzyme assay technique. In addition, our study could not differentiate between pasture, grassland, and forage fields due to the inadequate spatial resolution of the satellite imagery and lack of reliable agricultural land use information.…”
Section: Changes In Toc and Poxc (2015/16 -2019/20)mentioning
confidence: 81%
“…It is likely that the availability of N substrate from N fertilizer, shorter duration of experiment, and medium‐textured soil favored AST activity in Sidney compared with absence of N fertilization treatment, longer duration of the experiment, and coarse‐textured soil in Froid. Several researchers (Klose & Tabatabai, 1991; Perez‐Guzman et al., 2021) reported that AST activity was related to SOM and STN.…”
Section: Resultsmentioning
confidence: 99%
“…Bowls et al (2014) reported that BG activity was associated with increased N availability and NAG activity associated with increased C availability. Some researchers (Caudle et al, 2020;Perez-Guzman et al, 2021;Reardon et al, 2019) demonstrated that BG and NAG activities were related to phospholipid-derived fatty acid (PLFA), KMnO 4 -extractable C (POXC), SOC, STN, and autoclaved citrate-extractable protein (ACEP). The NAG activity was correlated to potentially mineralizable N (PMN), SOC, microbial biomass C, and PLFA (Muruganandan et al, 2009).…”
Section: Core Ideasmentioning
confidence: 99%
See 1 more Smart Citation
“…Shorter crop rotations, especially when including low residue crops such as soybean or potato, leads to a decline in SOC stocks as found in more intensive farming systems in Eastern Canada (Nyiraneza et al, 2017;Perez-Guzman et al, 2021). More diverse or extended crop rotations are recommended in organic farming systems, to maintain and enhance SOC, although this practice on farm may vary with scale and intensity of the farm operation (Lynch et al, 2014a;Lynch, 2015).…”
Section: Soil Organic Carbon and Soil Healthmentioning
confidence: 99%